2010
DOI: 10.1111/j.1467-971x.2009.01628.x
|View full text |Cite
|
Sign up to set email alerts
|

English in Cambodia: changes and challenges

Abstract: This paper reports research undertaken at a prestigious university in Phnom Penh in late 2007. The views of lecturers who teach the BEd (TEFL) degree and their students were canvassed in relation to the status of English in Cambodia. The students completed a questionnaire probing their views on the notion of a Cambodian English, as well as their preferences for learning different varieties of English. The lecturers discussed similar questions to those of the student questionnaires, but with more probing of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…It has been integrated into secondary school curricula (Clayton, 2006;Neau, 2003;Pit & Roth, 2003) and more recently into those of primary schools (Kuch, 2013). The English language is now taught by Cambodian ELT teachers across the country, compared to two decades ago when it was mostly taught by native English-speaking expatriates (Moore & Bounchan, 2010). A number of research papers have been published on various aspects of ELT in Cambodia, but very few have focused on learner autonomy (LA).…”
Section: Learner Autonomy In Cambodiamentioning
confidence: 99%
“…It has been integrated into secondary school curricula (Clayton, 2006;Neau, 2003;Pit & Roth, 2003) and more recently into those of primary schools (Kuch, 2013). The English language is now taught by Cambodian ELT teachers across the country, compared to two decades ago when it was mostly taught by native English-speaking expatriates (Moore & Bounchan, 2010). A number of research papers have been published on various aspects of ELT in Cambodia, but very few have focused on learner autonomy (LA).…”
Section: Learner Autonomy In Cambodiamentioning
confidence: 99%
“…In some Asian contexts, such as India and Pakistan, new Englishes are widely recognised while in others, such as Japan, where English is mainly used as a foreign language, the awareness and acceptance of WE are lower. Suzuki (2011) Among several studies in ASEAN contexts, Moore and Bounchan (2010) examined Cambodian English by employing questionnaires and focus group interviews. The study investigated the perceptions of teachers, administrators, and students as to the status of Cambodian English, and their preferences for different kinds of English.…”
Section: Previous Studies In Asian Contextmentioning
confidence: 99%
“…Young Cambodians, he added, are already using this blend of language-learning input to create successful communication for personal, educational, and work-related purposes. Moore and Bounchan's (2010) survey of the opinions of students at the Institute of Foreign Languages at the Royal University of Phnom Penh regarding the value of Cambodian ELT faculty there found that a growing minority of learners appreciated the value of Cambodian teachers of English because of "how they could help their students to learn English, whereas native English speakers seem to be valued only as role models for English pronunciation and spoken interaction" (p. 123). While this finding might not hold true in other settings, the possible emergence of a trend is an intriguing area for future research.…”
Section: Moving Toward a Multilingual Model Of Elt In Cambodia And Thmentioning
confidence: 99%